Molecular taxonomy of Vicia L. species (Fabaceae) from the mountainous regions of Iraqi Kurdistan based on ITS barcoding - Al-Taie, Ali Talib; Golparvar, Ahmad Reza; Hasan, Muazaz Azeez; Darbaghshahi, Mohammad Reza Naderi (Phytotaxa, 2025)
Accurate species identification within Vicia remains challenging due to high morphological variability, phenotypic plasticity, and frequent hybridization. This study presents the first molecular assessment of nine wild Vicia species from the mountainous area of Iraqi Kurdistan using the ITS region. A dataset of 32 ITS sequences (nine Iraqi accessions and 23 GenBank references) was analyzed for genetic divergence and species discrimination. Intraspecific K2P distances ranged from 0.002 to 0.018, while interspecific distances varied from 0.005 to 0.111, generally exceeding intraspecific divergence. Barcode gap analysis revealed a clear species-level separation in Vicia ervilia L., Vicia faba L., Vicia. narbonensis L., and Vicia sericocarpa Fenzl, whereas only partial overlap was observed in Vicia tenuifolia Roth., Vicia villosa Roth., Vicia palaestina Boiss., Vicia michauxii Spreng., and Vicia sativa L. The species identification tests (TaxonDNA) offered approximately 90% correct assignments, but the All-Species Barcode provided only 56% of correct assignments, reflecting the loss of resolution of closely related taxa. Maximum Likelihood phylogenetic inference confirmed that most Iraqi accessions clustered with conspecific references from neighboring countries. However, the weak support for some lineages raised questions about the resolving power of ITS for assessing recently diverged or hybridizing taxa. Generally, ITS barcodes were suitable for confirming the species identity and phylogenetic reconstruction of Iraqi Vicia but were insufficient to completely resolve the closely related lineages. This study provides the first molecular dataset for Vicia in Iraq and underscores the need for multilocus or genomic-scale approaches to solidify species delimitation and support regional plant genetic resource conservation.